The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages were discovered, without much regard to the total effect on either patient or doctor. Medicine itself was becoming departmentalised. The family doctor, working single-handed or in a small partnership, usually had too much to do because he had too many patients, insufficient help, and insufficient equipment, and he was unable except with great difficulty to keep up to date or to enjoy reasonable leisure. Surrounded by a host of services and schemes managed in different ways by different public and voluntary authorities not themselves working to any clear common plan, the doctor has often been almost as bewildered as his patients. Specialists and consultants in order to make a living — for they have hardly ever been paid for their work in the voluntary hospitals — were obliged to charge their private patients heavy fees, and to settle in towns and districts where people able to afford those fees were numerous. Over wide areas of the country this made it difficult for any but wealthy patients to obtain their services. In place of this multiplicity there is now a unified Service available for the medical care of all citizens, regardless of class or income. The new Service is there for everyone who wants to use it, and is designed to be the normal way for people to get all the advice and help they need. But, as has already been briefly explained, there is no sort of compulsion. Anyone is free to make his own private arrangements if he so prefers ; or to use the Service for some purposes, such as hospital care, while making private arrangements for other purposes, such as sight-testing and the obtaining of spectacles, or dentistry (a patient who chooses to pay a doctor, however, must also pay to have his prescription made up at the chemists — because the medicine cannot be regarded as separable from the doctor's advice and treatment). In the same way, any doctor is free, if he wishes, to stay outside, confining his practice to patients who want to pay fees ; and he is also free to work partly in the Service and partly in private practice. As in the past, the citizen remains free to choose, and change, his personal doctor, and the doctor remains free to accept or refuse a patient. How the National Bill is Paid The national doctor's bill — the cost of the whole range of services — is paid mainly out of rates and taxes. (A minor part comes from insurance contributions as well; but insurance is not a condition of using the Health Service, which is open to all.) For the services provided by the 146 Local Health Authorities the money comes partly from the rates and partly from Government grants. By paying in advance (indirectly, as a taxpayer, etc.) the citizen spares himself any personal payment when he uses the Service. There is no charge for any advice, treatment, 4 21/1489